Determination of Marketing Strategy Priority in the Tofu Processing Industry Using Analytical Hierarchy Process (AHP) Method (Case Study of Wakobalu Agung Village, Kabangka District, Muna Regency) - Ilham La Ode; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to obtain the highest goals and weights from the marketing strategy in the tofu industry in Wakobalu Agung Village, Kabangka District, Muna Regency, using the AHP method to obtain stakeholders from the marketing strategy in the tofu industry in Wakobalu Agung Village, Kabangka District, Muna Regency using the AHP method, To get the alternative and the highest weight of the marketing strategy in the tofu industry using the AHP method. Data collection is done by interview method, questionnaire/questionnaire technique, and documentation. The results showed that the marketing strategy of the tofu processing industry increased the importance of each goal, namely increasing income with a weighted value of (0.394), increasing demand with a weighted value of (0.303), improving product quality with a weighted value of (0.187), and rising competitive price with a weighted value of (0.116). The level of importance of each stakeholder is the tofu industry with a weighted value of (0.435), Farmers with a weighted value of (0.204), the government with a weighted value of (0.173), academics with a weighted value of (0.094) and finance with a value of (0.093). The marketing strategy in the tofu industry for each stakeholder is the tofu industry with a weighted value of (0.435), farmers with a weighted value of (0.204), the government with a weighted value of (0.173), academics with a weighted value of (0.094) and finance with a value of (0.093). The alternative assessment resulted in the highest weighting successively product development strategy with a value of (0.579), market share increase strategy (0.234), improvement strategy, and utilization of existing resources (0.187).